The role and mechanisms of intraocular infusion during microinvasive guillotine and ultrasonic vitrectomy - B.M. Aznabaev; T.R. Mukhamadeev; T.I. Dibaev; T.N. Ismagilov (РМЖ "Клиническая офтальмология")
B.M. Aznabaev1,2, T.R. Mukhamadeev1,2, T.I. Dibaev1,2, T.N. Ismagilov1,2 1Bashkir State Medical University, Ufa, Russian Federation 2CJSC Optimedservis, Ufa, Russian Federation Maintaining tone of the eyeball and stable intraocular pressure (IOP) during vitrectomy is an important issue associated with the safety of intraocular structures. As the vitreous body is removed, it is gradually replaced with a balanced salt solution, which leads to a decrease in viscosity of the vitreous chamber content and may contribute to changes of the hydrodynamic parameters during surgical procedures. Thus, it is necessary to ensure controlled operation and coordination of the infusion and aspiration modules used in the microsurgical system. Commonly, the imbalance between the aqueous humor inflow and outflow during vitrectomy may cause either a decrease or increase in IOP. The gravity infusion surgical systems cannot compensate for sudden changes in the hydrodynamic parameters during eye surgery, and, as a result, significant fluctuations in IOP may occur. Thus, it is important to develop algorithms for forced infusion that will ensure a more precise control of the infusion flow. The review describes various forced infusion mechanisms and key approaches to their use, as well as their effectiveness and safety patterns, highlighted in the experimental and clinical studies. Keywords: vitrectomy, intraocular pressure, hydrodynamic balance, forced infusion, microsurgical systems, ultrasonic vitrectomy. For citation: Aznabaev B.M., Mukhamadeev T.R., Dibaev T.I., Ismagilov T.N. The role and mechanisms of intraocular infusion during microinvasive guillotine and ultrasonic vitrectomy. Russian Journal of Clinical Ophthalmology. 2023;23(1):66–70 (in Russ.). DOI: 10.32364/2311-7729-2023-23-1-66-70.